The Clinical Role of Inflammatory Chemokine RANTES (CCL5) in a Sample of COVID-19 Baghdad Province Patients - Zahra'a Abdul AL-Aziz Yousif; Jabbar S. Hassan; Ghaith H. Hameed (Iraqi Journal of Pharmaceutical Sciences, 2025)
COVID-19 disease is a clinical syndrome caused by an envelope RNA virus, called SARS-COV-2., which causes infection with wildly clinical pictures. Through COVID-19 infection several components of humoral and cellular immune response have an important role in the progression of the infection. Chemokines are one of the inflammatory mediators that play an essential role in the immune pathogenesis of COVID-19. It is secreted by respiratory virus-infected cells in the upper respiratory tract, causing stimulation and recruitment of inflammatory cells such as neutrophils, NK, eosinophils, and macrophages from the bloodstream to the site of the infection. This study strives to determine the impact role of inflammatory mediator chemokine RANTES (CCL5) in COVID-19 Iraq patients. Blood samples collected from 180 individuals were enrolled in this study, 120 of them were patients infected with COVID-19 and verified by reverse transcriptase polymerase chain reaction (RT-PCR). The patients were categorized into two groups based on the severity of the disease, the severe group included 60 patients and the mild/moderate group included 60 patients also. Furthermore, 60 healthy individuals who were confirmed to be COVID-19-negative were enrolled in this study as a control group. The quantitative detection of CCL5 in human serum was done by the CCL5 Enzyme Linked Immune Sorbent Assay kit based on the principle of sandwich ELISA. This study showed that there were interesting highly significant differences (p<0.001) in the median serum level of CCL5 between all groups that participated in this study and there was a significant increase in the median level of CCL5 in control and mild-moderate groups versus severe patients’ group (66.66 pg/ml, and 54.04 pg/ml vs. 38.41 pg/ml respectively). According to the results of this study, the low level of CCL5 associated with COVID-19 severity infection could be used as a predictor marker for severity while the elevated level of CCL5 in control and mild-moderate suggested the elevated level of this chemokine is likely to be associated with the resolution of inflammation and recovery.